Confined Mobility of TonB and FepA in Escherichia coli Membranes - Lill, Y.; Jordan, L. D.; Smallwood, C. R.; Newton, Salete M.; Lill, M. A.; Klebba, Phillip E.; Ritchie, K. (My University, 2016)
The important process of nutrient uptake in Escherichia coli, in many cases, involves transit of the nutrient through a class of beta-barrel proteins in the outer membrane known as TonB-dependent transporters (TBDTs) and requires interaction with the inner membrane protein TonB. Here we have imaged the mobility of the ferric enterobactin transporter FepA and TonB by tracking them in the membranes of live E. coli with single-molecule resolution at time-scales ranging from milliseconds to seconds. We employed simple simulations to model/analyze the lateral diffusion in the membranes of E. coli, to take into account both the highly curved geometry of the cell and artifactual effects expected due to finite exposure time imaging. We find that both molecules perform confined lateral diffusion in their respective membranes in the absence of ligand with FepA confined to a region 0.180(-0.007)(+0.006) mu m in radius in the outer membrane and TonB confined to a region 0.266(0.009)(+0.007) mu m in radius in the inner membrane. The diffusion coefficient of these molecules on millisecond time-scales was estimated to be 21(-5)(+9) mu m(2)/s and 5.4(-0.8)(+1.5) mu m(2)/s for FepA and TonB, respectively, implying that each molecule is free to diffuse within its domain. Disruption of the inner membrane potential, deletion of ExbB/D from the inner membrane, presence of ligand or antibody to FepA and disruption of the MreB cytoskeleton was all found to further restrict the mobility of both molecules. Results are analyzed in terms of changes in confinement size and interactions between the two proteins.
Citation: Lill, Y., Jordan, L. D., Smallwood, C. R., Newton, S. M., Lill, M. A., Klebba, P. E., & Ritchie, K. (2016). Confined Mobility of TonB and FepA in Escherichia coli Membranes. Plos One, 11(12), 18. doi:10.1371/journal.pone.0160862
Keywords: Single-Molecule Tracking; Ferric Enterobactin Transport; Bacterial; Outer-Membrane; Gram-Negative Bacteria; Crystal-Structure